2014
DOI: 10.1111/jsm.12399
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Functioning and Vaginal Changes after Radical Vaginal Trachelectomy in Early Stage Cervical Cancer Patients: A Longitudinal Study

Abstract: Introduction Radical vaginal trachelectomy (RVT) offers low complication rate, good survival, and possibility for future childbearing for young women with early stage cervical cancer. However, the literature on quality of life (QOL) and sexual functioning in patients undergoing RVT is scarce. Aim The aims of this study were to prospectively assess sexual function after RVT and to compare scores of sexual function in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 30 publications
3
59
1
3
Order By: Relevance
“…It is possible that a smaller difference could still exist. Our data are further supported by an additional longitudinal study of young cervical cancer patients who underwent trachelectomy also showed similar sexual dysfunction as patients who underwent radical hysterectomy 12 months after surgery [14].…”
Section: Accepted Manuscriptsupporting
confidence: 71%
“…It is possible that a smaller difference could still exist. Our data are further supported by an additional longitudinal study of young cervical cancer patients who underwent trachelectomy also showed similar sexual dysfunction as patients who underwent radical hysterectomy 12 months after surgery [14].…”
Section: Accepted Manuscriptsupporting
confidence: 71%
“…In agreement with our previous findings, it may be concluded that patients treated with RVT are equally affected both regarding urological dysfunction and lymphedema as patients treated with RAH. 11 Our present and former study highlights the importance of presurgery and postsurgery information and counseling of the patient. 11 The current study demonstrates that radical surgery for early-stage cervical cancer may permanently affect the patient postoperatively.…”
Section: Discussionmentioning
confidence: 54%
“…11 Our present and former study highlights the importance of presurgery and postsurgery information and counseling of the patient. 11 The current study demonstrates that radical surgery for early-stage cervical cancer may permanently affect the patient postoperatively. Our results highlight the necessity to critically evaluate the available evidence regarding treatment options for early-stage cervical cancer.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Radical trachelectomy is a safe fertility-sparing surgical option for some women with early-stage cervical cancer who have not completed childbearing [33-36]. Longitudinal comparisons in patients treated with radical trachelectomy versus radical hysterectomy showed no differences in mood, distress, sexual function, and QoL [9, 37]. Many women in both treatment groups faced depression, distress, and sexual dysfunction, although improvement over time was noted in these domains.…”
Section: Impact Of Gynecologic Cancer On Sexual Healthmentioning
confidence: 99%